2022
DOI: 10.26740/jptt.v13n2.p180-194
|View full text |Cite
|
Sign up to set email alerts
|

Peran Work Engagement Pada Hubungan Kepemimpinan Transformasional Dengan Organizational Citizenship Behavior Dosen Milenial

Abstract: Currently, many lecturer positions have been filled by millennials, even in 2025, the number of millennial workers will reach 75%, which means three out of four workers are millennials (Brant, 2019). Previous studies have shown that there are differences in the work values of the millennial and previous generations. This difference in work values will make millennial workers likely to avoid organizational citizenship behavior (OCB), even though OCB is a significant indicator of organizational performance (Pods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
1
0
3
Order By: Relevance
“…With this behavior, employees with employee engagement will provide more performance to their organization because awareness of their role in the company and a sense of joy at work makes employees want to return to their jobs where employees can offer to help their co-workers and create extra-role or OCB behavior. This is in line with previous research by (Wulandari, 2021); (Farid et al, 2019); (Paredes et al, 2021); (Hariq and Mulyani, 2021), (Sofiah et al, 2022) concludes that there is a positive and significant relationship between work engagement and organizational citizenship behavior. Meanwhile, the results of the research (Affandi et al, 2019) show that work engagement has no significant effect on organizational citizenship behavior…”
Section: Discussionsupporting
confidence: 91%
“…With this behavior, employees with employee engagement will provide more performance to their organization because awareness of their role in the company and a sense of joy at work makes employees want to return to their jobs where employees can offer to help their co-workers and create extra-role or OCB behavior. This is in line with previous research by (Wulandari, 2021); (Farid et al, 2019); (Paredes et al, 2021); (Hariq and Mulyani, 2021), (Sofiah et al, 2022) concludes that there is a positive and significant relationship between work engagement and organizational citizenship behavior. Meanwhile, the results of the research (Affandi et al, 2019) show that work engagement has no significant effect on organizational citizenship behavior…”
Section: Discussionsupporting
confidence: 91%
“…Research conducted by Sulea, et al ( 2012) also shows the same thing. Research conducted by Sofiah, et al (2022) found that work engagement has a positive and significant effect on OCB. In line with research conducted by Kurniawati (2018) that work engagement has a positive and significant effect on OCB.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Sehingga para guru mampu menumbuhkan motivasi untuk dapat bekerja bersama dan mendukung organisasi secara sukarela dalam mencapai tujuan. Selaras dengan pemikiran Sofiah et al, (2022) yang menyampaikan bahwa kepemimpin transformasional itu berorientasi jangka panjang dan relevan dengan OCB, pemimpin yang peduli pada bawahan, mengarahkan dan memotivasi dengan menunjukkan bahwa segala pekerjaan adalah bermakna dan menantang sehingga bawahan menjadi bahagia. Terlebih, di era revolusi industri 4.0 sangat dibutuhkan seorang guru yang terampil dan mau saling berbagi.…”
Section: Metode Penelitianunclassified